Bromodomain and Extraterminal Proteins as Novel Epigenetic Targets for Renal Diseases - Morgado-Pascual, Jose Luis; Rayego-Mateos, Sandra; Tejedor, Lucia; Suarez-Alvarez, Beatriz; Ruiz-Ortega, Marta (Frontiers in Pharmacology, 2019)
Epigenetic mechanisms, especially DNA methylation and histone modifications, are dynamic processes that regulate the gene expression transcriptional program in normal and diseased states. The bromodomain and extraterminal (BET) protein family (BRD2, BRD3, BRD4 and BRDT) are epigenetic readers that, via bromodomains, regulate gene transcription by binding to acetylated lysine residues on histones and master transcriptional factors. Experimental data have demonstrated the involvement of some BET proteins in many pathological conditions, including tumor development, infections, autoimmunity and inflammation. Selective bromodomain inhibitors are epigenetic drugs that block the interaction between BET proteins and acetylated proteins, thus exerting beneficial effects. Recent data have described the beneficial effect of BET inhibition on experimental renal diseases. Emerging evidence underscores the importance of environmental modifications in the origin of pathological features in chronic kidney diseases (CKD). Several cellular processes such as oxidation, metabolic disorders, cytokines, inflammation, or accumulated uremic toxins may induce epigenetic modifications that regulate key processes involved in renal damage and in other pathological conditions observed in CKD patients. Here, we review how targeting bromodomains in BET proteins may regulate essential processes involved in renal diseases and in associated complications found in CKD patients, such as cardiovascular damage, highlighting the potential of epigenetic therapeutic strategies against BET proteins for CKD treatment and associated risks.